Assessing Movement Competence and Screening for Injury Risk in 8–12-year-Old Children: Reliability of the Child-Focused Injury Risk Screening Tool (ChildFIRST). Issue 3 (2nd July 2020) - Miller, Matthew B.; Jimenez-Garcia, John Alexander; Hong, Chang Ki; DeMont, Richard
ABSTRACT: The Child-Focused Injury Risk Screening Tool (ChildFIRST) is a process-based assessment including 10 movement skills with 4 associated evaluation criteria. The ChildFIRST has been validated by a group of experts to evaluate movement competence and injury risk in 8–12-year-olds. The purpose of this study is to evaluate the reliability of the ChildFIRST. Twelve college-aged subjects participants attended a 1-hr training session. To evaluate inter-rater reliability, the participants rated 6 videos per movement, 60 videos in total. To evaluate intra-rater reliability, the participants returned after 7 days to rate the same videos. Movement skill inter-rater reliability ranged from −0.306 to 9.380 ICC, intra-rater reliability ranged from −0.386 to 0.881 ICC. Evaluation criteria inter-rater reliability ranged from −0.04 to 0.835 Kα and 52–100% agreement, intra-rater reliability ranged from −0.328 to 0.303 Cohen's K and 45.8–98.6% agreement. The ChildFIRST demonstrates moderate-to-excellent inter-rater reliability for 9 of 10 movement skills, while intra-rater reliability and overall evaluation criteria reliability range from good to poor.